Biomechanical correlates of zygomaxillary-surface shape in papionin primates and the effects of hard-object feeding on mangabey facial form. Issue 163 (February 2022) - Singleton, Michelle; Ehrlich, Daniel E.; Adams, Justin W.
Abstract: Extant African papioninans are distinguished from macaques by the presence of excavated facial fossae; however, facial excavation differs among taxa. Mangabeys ( Cercocebus, Rungwecebus, and Lophocebus ) exhibit fossae that invade the zygomatic forming pronounced suborbital fossae (SOFs). Larger-bodied Papio, Mandrillus, and Theropithecus have lateral rostral fossae with minimal/absent suborbital fossae. Because prior studies have shown that mangabeys exhibit adaptations to anterior dental loading (e.g., palatal retraction), it is plausible that mangabey SOFs represent structural accommodation to masticatory-system shape rather than facial allometry, as commonly hypothesized. We analyzed covariation between zygomaxillary-surface shape, masticatory-system shape, and facial size in 141 adult crania of Macaca fascicularis, Papio kindae, Cercocebus, and Lophocebus . These taxa represent the range of papionin SOF expression while minimizing size variation (narrow allometry). Masticatory-system landmarks (39) registered palate shape, bite points, masticatory muscle attachments, and the temporomandibular joint. Semilandmarks (450) captured zygomaxillary-surface shape. Following Procrustes superimposition with semilandmark sliding and principal components analyses, multivariate regression was used to explore allometry, and two-block partial least-squares analyses (within-configuration and separate-blocks) were used to examine covariation patterns. Scores on principal components 1–2 and the first partial least-square (PLS1) separate mangabeys from Macaca and Papio . Both zygomaxillary-surface shape and masticatory-system shape are correlated with size within taxa and facial morphotypes; however, regression distributions indicate morphotype shape differences are non-allometric. PLS1 accounts for ∼95% of shape covariance ( p  < 0.0001) and shows strong linear correlations (r-PLS = ∼0.95, p  < 0.0001) between blocks. Negative PLS1 scores in mangabeys reflect deep excavation of the suborbital malar surface, palatal retraction, and anterior displacement of jaw adductor muscles and the temporomandibular joint. Neither PC1 nor PLS1 scores ordinate specimens by facial size. Taken together, these results fail to support the allometric hypothesis but suggest that mangabey zygomaxillary morphology is closely linked with adaptations to hard-object feeding.